Embankments on soft soil reinforced with stone columns: numerical analysis and proposal of a new design method - José Leitão Borges (2009)
A parametric study of an embankment on soft soils reinforced with stone columns is performed using a computer program based on the finite element method. The cylindrical unit cell formulation is used by modeling one column and its surrounding soft soil with confined axisymmetric behaviour. The computer program incorporates the Biot consolidation theory (coupled formulation of the flow and equilibrium equations) with constitutive relations simulated by the p-q- critical state model. The following parameters are analysed: the replacement area ratio, the deformability of the column material, the thickness of the soft soil, the deformability of the fill and the friction angle of the column material. Based on the results of this study, a new design method is proposed, relating the settlement improvement factor to the two factors that revealed major influence: the replacement area ratio and the ratio between the deformability of the soft soil and the deformability of the column material.